Activation of insulin‐like growth factor‐1 receptor confers acquired resistance to osimertinib in non‐small cell lung cancer with EGFR T790M mutation - Daisuke Hayakawa; Fumiyuki Takahashi; Yoichiro Mitsuishi; Ken Tajima; Moulid Hidayat; Wira Winardi; Hiroaki Ihara; Koichiro Kanamori; Naohisa Matsumoto; Tetsuhiko Asao; Ryo Ko; Takehito Shukuya; et al. (Thoracic Cancer, 2020)
Abstract Background Osimertinib (AZD9291) is a third‐generation EGFR‐tyrosine kinase inhibitor (TKI) that selectively inhibits the activating EGFR mutation and T790M mutation, and is currently used globally to treat EGFR‐mutant non‐small cell lung cancer (NSCLC). However, acquired resistance to osimertinib is inevitable. Methods We established osimertinib‐resistant cells (PC9/T790M/AZDR and H1975/AZDR) derived from EGFR‐mutant NSCLC cells harboring T790M mutation, and investigated the mechanism of acquired resistance to osimertinib by whole‐exome sequencing and multiple phospho‐receptor tyrosine kinase (RTK) array. A tumor specimen from an EGFR‐mutant NSCLC patient with acquired resistance to osimertinib was also subjected to immunohistochemical analysis. Results Whole‐exome sequencing analysis demonstrated that genetic alterations, such as acquisition of EGFR C797S, loss of T790M mutation, MET amplification, or mutated KRAS, MEK, BRAF, PIK3CA, were not detected. Analysis of phospho‐RTK array revealed that insulin‐like growth factor‐1 receptor (IGF1R) was activated in PC9/T790M/AZDR and H1975/AZDR cells. Knockdown of IGF1R by siRNA as well as inhibition of IGF1R activation by linstinib (IGF1R inhibitor) significantly restored the sensitivity to osimertinib. Immunohistochemical analysis revealed that the expression level of phosphorylated IGF1R was higher in the tumor specimen from the EGFR‐mutant NSCLC patient with acquired resistance to osimertinib than in the specimen collected prior to the treatment. Conclusions IGF1R activation could occur following treatment with osimertinib in EGFR‐mutant NSCLC with T790M mutation, and might be one of the mechanisms underlying osimertinib resistance. Combined treatment of osimertinib and IGF1R inhibitor might be effective in overcoming the acquired resistance to osimertinib induced by IGF1R activation. Key points Significant findings of the study: Using osimertinib‐resistant cells, we found that IGF1R activation induced by osimertinib treatment in EGFR‐mutant NSCLC with T790M mutation is involved in resistance. Increased phosphorylation of IGF1R was observed in the tumor specimen from an EGFR‐mutant NSCLC patient with acquired osimertinib resistance. What this study adds: IGF1R activation might be one of the mechanisms of osimertinib resistance. A combination therapy with osimertinib and an IGF1R inhibitor might be an optimal approach for overcoming the acquired resistance to osimertinib induced by IGF1R activation.